2023
DOI: 10.3389/fphar.2023.1185809
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine use is associated with lower risk of pneumonia in patients with systemic lupus erythematosus: a population-based retrospective cohort study

Abstract: Objectives: To investigate the association between traditional Chinese medicine (TCM) therapy and the risk of pneumonia in patients with systemic lupus erythematosus (SLE).Methods: This population-based control study analyzed the data retrieved from the National Health Insurance Research database in Taiwan. From a cohort of 2 million records of the 2000–2018 period, 9,714 newly diagnosed patients with SLE were initially included. 532 patients with pneumonia and 532 patients without pneumonia were matched 1:1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In line with previous research (Ma et al, 2016;Chen et al, 2022;Chen et al, 2023;Ma et al, 2023), our findings indicated that patients receiving the 17 PRCHMSLE may experience a reduction in all-cause mortality, a lower incidence of ESRD, fewer hospital admissions, and no potential for an increase in the risk of hyperkalemia. We also identified a lower risk of noncardiovascular mortality in patients with SLE-CKD using PRCHMSLE compared to nonusers, mirroring findings from a previous NHI-based cohort study that indicated a reduced risk of pneumonia in patients with SLE using CHMs compared to nonusers (Wang et al, 2023). However, our results did not demonstrate a significant reduction in the risk of Frontiers in Pharmacology frontiersin.org cardiovascular mortality in patients with SLE-CKD using PRCHMSLE.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In line with previous research (Ma et al, 2016;Chen et al, 2022;Chen et al, 2023;Ma et al, 2023), our findings indicated that patients receiving the 17 PRCHMSLE may experience a reduction in all-cause mortality, a lower incidence of ESRD, fewer hospital admissions, and no potential for an increase in the risk of hyperkalemia. We also identified a lower risk of noncardiovascular mortality in patients with SLE-CKD using PRCHMSLE compared to nonusers, mirroring findings from a previous NHI-based cohort study that indicated a reduced risk of pneumonia in patients with SLE using CHMs compared to nonusers (Wang et al, 2023). However, our results did not demonstrate a significant reduction in the risk of Frontiers in Pharmacology frontiersin.org cardiovascular mortality in patients with SLE-CKD using PRCHMSLE.…”
Section: Discussionsupporting
confidence: 83%
“…Notably, the top five treatments offering the most renal protection were Gan-Lu-Ying, Anemarrhena asphodeloides Bunge [Asparagaceae; Rhizoma Anemarrhenae] (Zhi-Mu), Rehmannia SLE is a complex disease affecting multiple bodily systems, including renal, cardiovascular, and pulmonary functions (Vymetal et al, 2016). Recent cohort studies using Taiwan's NHI claims data have spotlighted potential benefits of CHMs in SLE management, indicating decreased risks of LN (Chang et al, 2017), mortality (Ma et al, 2016), cardiovascular disease (Yu and Hsieh, 2021), pneumonia (Wang et al, 2023), and hospitalization (Ma et al, 2023). Significantly, LN is a chief factor in SLE-related deaths (Sciascia et al, 2017).…”
Section: Discussionmentioning
confidence: 99%